Анализ внешних атак на локальную сеть и возможностей защиты реконфигурируемые устройства - Коростиль, Ю.М.; Давиденко, А.Н.; Гильгурт, С.Я.; Панченко, М.М. (Моделювання та інформаційні технології, 2010)
The utilization of programmable logic for defense of local area network from
external attacks is investigated. Specific threats from internet to local computers and
possibilities of FPGA-based digital equipment to parry them are discussed.